Association Between Spinopelvic Alignment and Reoperation Following Percutaneous Transforaminal Endoscopic Decompression: A Matched Case-Control Study - Ge Y; Wang A; Song H; Fan N; Zang L (Journal of Pain Research)
Yang Ge, Aobo Wang, He Song, Ning Fan, Lei Zang Department of Orthopedics, Beijing Chaoyang Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Lei Zang, Department of Orthopedics, Beijing Chaoyang Hospital, 5 JingYuan Road, Shijingshan District, Beijing, 100043, People’s Republic of China, Email zanglei@ccmu.edu.cnPurpose: Percutaneous transforaminal endoscopic decompression (PTED) is widely used for treating lumbar spinal stenosis (LSS), yet predictors of reoperation remain unclear. This study aimed to explore the association between spinopelvic alignment and the reoperation following PTED.Patients and Methods: A 1:2 matched case-control study was conducted, involving patients who underwent single-level PTED for LSS at our institution from May 2014 to August 2022. Cases comprised patients requiring reoperation after initial PTED, while controls were those without reoperation during the follow-up. Measured radiological parameters included pelvic tilt (PT), pelvic incidence (PI), sacral slope (SS), lumbar lordosis (LL), mismatch between pelvic incidence and lumbar lordosis (PI-LL), disc height (DH), Pfirrmann classification, and Modic changes (MCs). Univariate and multivariate logistic regression analyses were performed to identify predictors. Receiver operating characteristic (ROC) curves were generated to determine cut-off points.Results: 76 cases and 152 controls were selected from 1967 enrolled patients. Both groups had an average age of 61 years, a male-to-female ratio of 43:33, and a mean BMI of 25.95 kg/m². No significant differences in baseline characteristics were found between groups. Multivariate analysis identified PT (OR = 1.061, P = 0.007), PI-LL (OR = 1.057, P = 0.021), and DH (OR = 1.194, P = 0.015) as independent risk factors for the reoperation. ROC analysis revealed PI-LL with an area under the curve (AUC) of 0.662 at a cut-off of 12.95° (95% CI = 0.582– 0.741), PT with an AUC of 0.685 at a cut-off of 21.98° (95% CI = 0.606– 0.763), and DH with an AUC of 0.602 at a cut-off of 8.22° (95% CI = 0.521– 0.683).Conclusion: PI-LL ≥ 12.95°, PT ≥ 21.98°, and DH ≥ 8.22° are independent risk factors for reoperation following PTED.Keywords: spinal stenosis, decompression, endoscopy, lordosis, lumbosacral region, case-control studies